Coherence, extreme risk spillovers, and dynamic linkages between oil and China's commodity futures markets. (15th June 2021) - Cui, Jinxin; Goh, Mark; Zou, Huiwen
Abstract: This paper investigates the time-frequency dependence, extreme risk spillovers, and dynamic linkages between oil and China's commodity futures markets, using wavelet coherence, quantile connectedness approach, and the DECO-FIAPARCH (1, d, 1) model. The results suggest that the oil market exhibits higher coherence with the copper, natural rubber, and fuel oil futures but low coherence with corn, soybean, soybean meal, and white sugar futures on a long-term scale. The crude oil market leads most of China's commodity futures. The results of the DECO model point to the time-varying and low average equicorrelations between oil and China's commodity futures. The total risk connectedness at the extreme lower quantile level (0.01) is higher than the conditional mean and conditional median level. WTI oil, Brent oil, soybean oil, and copper futures are the main spillover net-transmitters whereas the white sugar, soybean, soybean meal, cotton, corn, aluminum, natural rubber, and fuel oil futures are risk spillover net-recipients. The dynamic extreme negative risk spillovers are highly volatile and vulnerable to major international events such as the GFC, oil price plunge, and the COVID-19 pandemic. Finally, Brent oil offers better portfolio diversification benefits than WTI oil and the optimal-weighted portfolio illustrates the highest risk and downside risk reduction effectiveness. Highlights: The wavelet coherence is applied to examine the time-frequency dependence. The novel quantile connectedness approach is employed to investigate the extreme risk spillovers. The DECO-FIAPARCH model is utilized to depict the dynamic equicorrelation. Hedging and portfolio effectiveness are evaluated based on the risk and downside risk reduction. The oil-commodity portfolios offer better but heterogeneous risk management effectiveness.